Captains All : Captains All, Part 1. - Jacobs, W. W. (William Wymark), 1863-1943; Owen, Will, 1869-1957 (Salt Lake City, UT : Project Gutenberg, 2004)
"Captains All" by W.W. Jacobs is a collection of humorous short stories written during the early 20th century. The book revolves around the lives and adventures of sailors, illustrating the themes of camaraderie, love, and the absurdities of life at sea and ashore. It captures the essence of the sailor's experience, delving into their struggles and quirks with a comedic flair. The story primarily focuses on Sam Small, a seasoned sailor who begins to court a widow named Mrs. Finch. His friends, Ginger Dick and Peter Russet, also compete for her affection, leading to a series of humorous encounters as they each attempt to impress her. The narrative highlights Sam's comical attempts to maintain his image as a captain despite questionable truths about his past. As the competition intensifies, revelations about Mrs. Finch's nine children come to light, leading Sam to reconsider his romantic pursuits and ultimately decide to return to sea, reflecting the theme of escapism prevalent in sailor life. The light-hearted language and lively dialogue contribute to the book's charm and comedic undertone. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by David Widger
Keywords: Humorous stories, English; England -- Social life and customs -- Fiction; River life -- Fiction